Performance characterization of Au–Ge solder ball bumps fabricated via the Pulsated Orifice Ejection Method - Wei Dong; Donghang Liu; Fumin Xu (Journal of Materials Research and Technology)
The Gold-28at% Germanium (Au-28at%Ge) eutectic alloy exhibits significant potential as a replacement for high-lead solder alloys due to its excellent mechanical properties and corrosion resistance. However, its widespread application is limited by inherent brittleness. In this study, Au–Ge eutectic solder balls were fabricated using a self-developed Pulsated Orifice Ejection Method (POEM) under Ar and He atmospheres. The resulting solder balls demonstrated smooth and dense surface morphologies, narrow size distributions (maximum standard deviation of target particle size: 3.02 μm), and sphericity exceeding 0.95. Compared to the Ar atmosphere, the superior heat transfer rate in the He atmosphere completely suppressed the precipitation and growth of primary Au and Ge phases, yielding a refined eutectic microstructure. Reflow soldering was performed under N2 using the fabricated Au–Ge solder balls and Electroless Nickel Immersion Gold (ENIG)-treated Al2O3 substrates. Post-reflow analyses revealed that interfacial reactions produced continuous Ni5Ge3 and NiGe intermetallic compounds (IMCs) layers, ensuring excellent interfacial stability and structural integrity for both solder ball types. Notably, solder balls prepared under the He atmosphere retained the eutectic state at the interface, devoid of significant Au-rich regions or Ge phase segregation. Concurrently, the IMCs layers exhibited greater continuity and uniformity, correlating with a 31.6 % enhancement in joint shear strength.